Studi Perencanaan Kolam Olak Tipe Bak Tenggelam Pada Peredam Energi Bendung, Jl. Terusan Kecubung, Kota Malang - Kause, Nicodemus Nitanel; Khaerudin, Dian Noorvy; Frida, Kiki (eUREKA : Jurnal Penelitian Mahasiswa Teknik Sipil dan Teknik Kimia, 2018)
ABSTRACT Energy dampers are part of the weir that serves to dampen the energy of the water flow through the weir. Most of the dam damages in Indonesia are caused by the local scouring that occurs continuously downstream of the weir. The local scour is caused by considerable potential energy due to the differences in water level upstream and downstream of the weir. Local scours occurring downstream of the weirs caused by high water levels from damming, endanger the construction of the weir itself. To prevent deep scouring of long energy dampers, a new energy damper is planned. The main factor of the deep scouring on the downstream of the dam is the energy damper that has not functioned optimally. In this research used damper type energy sink. In the design of energy damper, based on flood water level +108,884 m, elevation of weir of +108,244 m, height of 2.5 m and flow rate 2,4217 m / sec found the condition of super critical flow during flood water and for dimension of energy damper: 8.25 m hydraulic jumping length, 1.86 m wake length, 2.75 m tube fingers and 2.35 m foundation depth. From the stable stability analysis of the dam to the bolsters, shear, the carrying capacity of the soil and the building does not decrease due to the load or soil stress that occurs. Keywords ; dams ; energy dampers ; hydraulic analysis ; stability.